Phytochemical screening, total flavonoid and phenolic content assays of various solvent extracts of fruit of persea americana mill. - Thant, Zin; U S., Mahadeva Rao (2018)
Background: Consumption of medicinal herbs protects and heals a number of ailments and they have been the principal treatment therapy in prehistoric times until the discovery of synthetic drugs. Objective: The objective of this research is to conduct the preliminary phytochemical screening, total flavonoid and phenolic contents assays of various, solvent extracts of fruit of Avocado. Method: Phytochemical screening was carried out according to the method of Trease and Evans, total flavonoid content was measured by the aluminium chloride colorimetric assay and total phenolic content was estimated spectrophotometrically by Folin-Ciocalteau method. Results:Preliminary phytochemical screening reveals the presence of phenolics, flavonoids, alkaloids, tannins, terpenoids in all the thee different' extracts (methanolic, ethanolic and aqueous). Methanolic extract has the richest content of both phenolics and flavonoids i.e. (4.27 mg GAE/g and 0'25 mg QE/g) respectively, and aqueous extract was the least i.e. (1.32 mg GAE/g and 0.164 mg QE/g)' All the extracts were not significantly different with one another (p > 0.05). Conclusion: It can be postulated that the contents of phenolic and flavonoid compounds of fruit of Avocado contribute to the radical scavenging activity and can be regarded as promising plant species for natural sources of antioxidant with potential value for treatment of many life threatening diseases. The process of extraction and identification of active principles responsible for the free radical scavenging property of various